Estimation of chronic dietary intake of pesticide residues - Jacqueline Mary Gerage Marques; Marina Vieira da Silva
ABSTRACT OBJECTIVE To estimate the maximum theoretical daily intake of pesticides potentially consumed, chronically, by the Brazilian population. METHOD By using data from the food consumption section of the 2008-2009 Household Budget Survey to characterize the population diet, a database was built to group the foods based on the NOVA classification. Considering the maximum residue limit values of each pesticide authorized in the country until 2016, the limits of all consumed foods were added and multiplied by the amount consumed, resulting in the maximum theoretical intake index, which was compared with the acceptable daily intake. RESULTS The results show that, of the 283 pesticides considered in the database, 71 (25%) compounds had estimates of zero intake, 144 compounds (50.8%) reached acceptable daily intake values and 68 compounds (24%) showed median intake that exceeded the acceptable daily value. The pesticide intake estimation according to the different regions of the country showed a variation in the amount of compounds that exceeded the acceptable daily intake (48 to 69 substances) due to the different consumption patterns. The categories of products that most exceeded the limits were the insecticides, herbicides and fungicides. CONCLUSION The application of this methodology is valid for the first step in risk assessment, but the resulting values may be different from the actual exposure since they do not include other factors, such as the combined use of pesticides or unauthorized products. The importance of developing research on specific national food consumption data in a systematic way is emphasized, which generates data and analyses that allow a detailed risk assessment.